Body weight gain and carcass yield of llamas (Lama glama) subjected to fattening under four feeding types - Robles, Ricardo (2020)
The aim of this study was to evaluate the bodyweight gain and carcass yield of young male llamas (milk tooth) subjected to fattening with four types of feeding (T1: Natural pasture; T2: T1 + vitamin injection; T3: T1 + alfalfa hay; T4: T2 + hay alfalfa). A completely randomized design with a 2x2 factorial arrangement with a covariance analysis (initial live weight as covariate) was used. Thirty-two llamas were randomized assigned to one of the four treatments for 84 days. The stocking rate was 1.3 animal units/ha. Daily weight gain (DWG) was evaluated in the fattening periods at 14, 28, 42, 56, 70 and 84 days. The DWG per fattening period was significantly different between periods, in the first three periods (14, 28 and 42 days) showing the best DWG (337, 237 and 160 g/d, respectively). The DWG per feed type was higher in T3 (157 g/d) during the 84-day period (p<0.01) and the best carcass yield was obtained in T4 (53.60%) followed by T3 (53.20%) (p<0.01). It is concluded that the highest DWG is achieved at day 42 and the best carcass yield is obtained with natural pasture + alfalfa hay supplementation (T3).